Gathering blue ebook - Lowry, Lois (The Giver Quartet, 2000)
The second book in Lois Lowry's Giver Quartet, which began with the bestselling and Newbery Medal-winning The Giver. Left orphaned and physically flawed in a civilization that shuns and discards the weak, Kira faces a frighteningly uncertain future. Her neighbors are hostile, and no one but a small boy offers to help. When she is summoned to judgment by The Council of Guardians, Kira prepares to fight for her life. But the Council, to her surprise, has plans for her. Blessed with an almost magical talent that keeps her alive, the young girl faces new responsibilities and a set of mysteries deep within the only world she has ever known. On her quest for truth, Kira discovers things that will change her life and world forever. A compelling examination of a future society, Gathering Blue challenges readers to think about community, creativity, and the values that they have learned to accept. Once again Lois Lowry brings readers on a provocative journey that inspires contemplation long after the last page is turned. "This extraordinary novel is remarkable for its fully realized characters, gripping plot, and Lowry's singular vision of a future." —VOYA The Giver has become one of the most influential novels of our time. Don't miss the powerful companion novels in Lois Lowry's Giver Quartet: Gathering Blue, Messenger, and Son.